Tata Kelola Rantai Nilai Gula Aren di Kabupaten Tasikmalaya (Jurnal Agribisnis Indonesia, 2024)
The high price of palm sugar compared to non-palm brown sugar at the consumer level raises the question of which value-creation activities cause the price of palm sugar to be relatively more expensive. This study aims (1) to identify the actors and the roles of each actor involved in the palm sugar value chain and (2) to analyse the governance formed in the value chain. This study uses primary data obtained through interviews with questionnaires and field observations. The sampling technique used snowball sampling with 53 palm sugar farmers and 10 palm sugar collectors as respondents. Data were analysed using descriptive qualitative, which refers to the global value chain analysis (GVC) proposed by Gereffi. The results showed that (1) the identified actors in the palm sugar value chain consisted of palm farmers, palm sugar processors, palm sugar collectors, traders, support services, social enterprises, and consumers. Palm sugar processors and collectors are the most important actors in the palm sugar value chain in Tasikmalaya Regency; (2) overall, the type of governance that is formed in the palm sugar value chain in Tasikmalaya Regency is modular governance.